Rhizosphere Cyanophyceae of Soybean Inoculated with Rhizobium Japonicum - U. Suriawiria (Institute for Research and Community Services (LPPM) ITB, 1972)
Abstract. A study has been made of the species of Cyanophyceae occurring in the rhizosphere and nonrhizosphere regions of soybeans in pot culture under glasshouse conditions. Eleven species of Cyanophyceae were detected. The algal species were not influenced in diversity by the presence of Rh. japonicum. Very few cells of only four species occurred in unplanted pots. Attention is drawn to the dearth of information available on rhizosphere algae and to their likely importance for the heterotrophic populations. Ringkasan. Penelitian terhadap species Cyanophyceae jang terdapat didaerah rhizosphere dan nonrhizosphere akar kedele, telah dilakukan dalam kondisi rumahkatja dengan menggunakan pot. Sebelas species Cyanophyceae telah didapatkan. Kehadiran Rh. japonicum ternjata tidak mempengaruhi diversitas species gang-gang. Hanja empat species dalam djumlah jang sangat sedikit, didapatkan pada pot tanpa kedele. Perhatian sangat ditundjukan karena kurangnja informasi mengenai ganggang didaerah rhizosphere, serta kepentingannja didalam populasi jang heterotropis.